Trends in learning global warming materials for supporting sustainable development goals: A bibliometric review - Aswiroh Aswiroh; Setyo Admoko (Momentum: Physics Education Journal, 2025)
Climate change and global warming are global issues with significant impacts on health, food security, and economic sustainability. This study aims to analyze learning trends related to global warming in support of the Sustainable Development Goals (SDGs) through a bibliometric approach. The research data were obtained from the Scopus database and analyzed using VOSviewer software. The findings indicate a significant increase in publications on global warming education from 2014 to 2024, with the highest number of publications recorded in 2024. Innovative learning models such as Problem-Based Learning (PBL), Project-Based Learning (PjBL), and Context-Based Learning (CBL) have proven effective in enhancing students’ scientific literacy, critical thinking, and communication skills regarding global warming issues. Universitas Pendidikan Indonesia has been identified as the leading institution contributing to this field. This study emphasizes the critical role of education in raising awareness and driving concrete actions against climate change. Furthermore, integrating global warming topics into formal education systems is a strategic measure to support climate change mitigation and environmental sustainability.